Cicil Emas pada Bank Syariah, Apakah Riba? - Dini, Sherina; Abbas, Ahmad; Ardiansyah (Milkiyah: Jurnal Hukum Ekonomi Syariah, 2024)
Gold that is traded can be a usurious item, so it is important for bank service providers to ensure that the process is in accordance with the principles of muamalat. This research discusses the gold product financing system provided by Islamic banks in installments and ensures that the transaction is in accordance with Islamic economic law. The type of research used is qualitative by utilizing a sociological approach in aspect of sharia economic law. Data collection using observation, interview and documentation methods. The research was conducted at BSI KCP Majene. The data that has been collected is analyzed by the method of data reduction, data presentation and conclusion drawing. The results of this study indicate that the gold installment system at BSI KCP Majene is carried out through 3 stages, namely the submission, the payment and the contract signing stages. In these stages, the use of murabahah contracts in the gold installment transactions under the BSI Cicil Emas product refers to Fatwa DSN-MUI Number 04/DSN-MUI/IV/2000. However, there is a problem in this stage where the practice resembles debt with the margin gained by BSI and it is classified as qard riba.